Social Construction of Non-Formal Education: Study on the Public Society in Jendela Lampung Community - Putri Ayu Fatmawati; Wawan Hernawan; Noning Verawati (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to describe the social construction of the Bakung TPA community towards non-formal education organized by the Jendela Lampung Community (KJL). The intended social construction is how they view the importance of non-formal education and how this can contribute to improving their quality of life based on the theory adapted by Peter L. Berger through three stages: externalization, objectivation, and internalization. The method used is a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. This study uses purposive sampling and snowball sampling techniques with several informants consisting of the coordinator and founder of the Jendela Lampung Community, parents and children who are active and inactive, and village officials. The results of the study show that the idea of non-formal education, which was initially a community initiative, developed into an activity that was accepted and supported by the wider community, including parents, community leaders, and the village government. Non-formal education was then internalized as an important need that complements formal education, especially in increasing learning interests and academic and social abilities of children in the environment, especially those who lack access to education. The implications of social identity theory and symbolic interactionism are also evident in the process of identity formation as a solid learning community. This research provides recommendations for the government, society, and future researchers to continue developing and supporting non-formal education as an inclusive and sustainable alternative and complement to formal education.